2005
DOI: 10.3928/1542-8877-20051101-06
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Combined Simultaneous Transpupillary Thermotherapy and ICG-Based Photodynamic Therapy for Choroidal Melanoma

Abstract: * BACKGROUND AND OBJECTIVE: To evaluate whether the combination of simultaneous hyperthermia by transpupillary thermotherapy and indocyanine green-based photodynamic therapy is an effective treatment for small and medium choroidal melanomas. * PATIENTS AND METHODS: Twenty-five patients with small and medium choroidal melanomas were treated with combined simultaneous transpupillary thermotherapy and indocyanine green-based photodynamic therapy. * RESULTS : The median age of the 25 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Other investigators also found a relationship between proximity of the tumor to the fovea and visual prognosis after primary TTT of choroidal 17,18,21,26 and retinal detachment. 10,13,16,18,21,27,28 Although a study comparing TTT with plaque radiotherapy failed to show any visual advantage to TTT, 10 we and some other investigators believe that TTT of certain small choroidal melanomas, especially those located close to but outside the central macula, may be associated with better long-term visual outcome compared with radiotherapy. 14 Of 108 recurrent tumors in this study, the majority were controlled by additional local treatment methods including TTT (20 [19%]), plaque radiation (60 [56%]), or proton beam radiation (2 [2%]) with enucleation necessary in 26 patients (24%) with tumor recurrence (4 other eyes required enucleation because of severe neovascular glaucoma; Table 3).…”
Section: Discussionmentioning
confidence: 91%
“…Other investigators also found a relationship between proximity of the tumor to the fovea and visual prognosis after primary TTT of choroidal 17,18,21,26 and retinal detachment. 10,13,16,18,21,27,28 Although a study comparing TTT with plaque radiotherapy failed to show any visual advantage to TTT, 10 we and some other investigators believe that TTT of certain small choroidal melanomas, especially those located close to but outside the central macula, may be associated with better long-term visual outcome compared with radiotherapy. 14 Of 108 recurrent tumors in this study, the majority were controlled by additional local treatment methods including TTT (20 [19%]), plaque radiation (60 [56%]), or proton beam radiation (2 [2%]) with enucleation necessary in 26 patients (24%) with tumor recurrence (4 other eyes required enucleation because of severe neovascular glaucoma; Table 3).…”
Section: Discussionmentioning
confidence: 91%
“…A total of 64 patients with choroidal melanoma were treated with ICG and in only one case was there no tumor regression (98% success). 101, 109, 131 Liggett et al 109 used a combination of simultaneous transpupillary thermotherapy and PDT in small-to medium-sized choroidal melanomas. Murillo Lopez et al 131 reported success in a case treated only with PDT.…”
Section: Choroidal Melanomamentioning
confidence: 99%
“…TTT delivers a low frequency 810 nm infrared diode laser, producing a temperature rise of 45–60°centigrade with an exposure of 1 min or longer 16. It has been reported to generate heat and uveal melanoma destruction to a depth of 4 mm17 but relies upon inherent pigmentation for adequate laser response.…”
Section: Discussionmentioning
confidence: 99%
“…With the addition of ICG-enhancement, there are two mechanisms at play: the thermal impact and a photodynamic effect. Hyperthermia is directly cytotoxic and induces apoptosis while also inhibiting angiogenesis 16. In addition, the photodynamic effect generates reactive oxygen, which induces irreversible damage to neoplastic cells and their vasculature 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation